Pengaruh Pendapatan Terhadap Penglibatan Muslim Dalam Filantropi Ketika Kesukaran Pandemik COVID-19: Income Factors in Influencing Muslim Philanthropic Behavior During the COVID-19 Pandemic - Mustafar, Mohd Zaid; Mohd Aziz , Mohd Khairul Nizam; Mohd Fadzil, Muhammad Faidz; Noor, Muaz Mohd (Online Journal of Research in Islamic Studies, 2022)
The COVID-19 pandemic that hit the country had a huge impact, especially on the economic sector. The movement control order (MCO) approach taken by the government to control the spread of epidemic infections indirectly impacts household income. However, some of the communities that are not affected in terms of income have the opportunity to be involved in charity to help those affected. Thus, this study aimed to examine the influence of income on Muslim involvement in philanthropy during the COVID-19 pandemic. To achieve this goal, 424 respondents responded to the questionnaires distributed during the MCO period as a time limit through a simple sampling method. The study’s results found that the income factor has a significant positive relationship based on the correlation value of r = 0.285 on the level of Muslim philanthropy involvement during the MCO period. The ANOVA test found significant differences based on the income level of Muslim philanthropic behavior among the respondents. These findings also prove that income influences the decision-making process to donate among Muslims. Therefore, all parties need to create awareness of the importance of philanthropic practices so that the burden borne by the community affected by the COVID-19 pandemic can be alleviated.